1994
DOI: 10.1016/0375-9601(94)00732-5
|View full text |Cite
|
Sign up to set email alerts
|

The Bianchi IX (mixmaster) cosmological model is not integrable

Abstract: The perturbation of an exact solution exhibits a movable transcendental essential singularity, thus proving the nonintegrability. Then, all possible exact particular solutions which may be written in closed form are isolated with the perturbative Painlevé test; this proves the inexistence of any vacuum solution other than the three known ones.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
63
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 34 publications
3
63
0
1
Order By: Relevance
“…In short, Lyapunov exponents are not reliable indicators of chaos in general relativity. Using a different approach, it was shown that the mixmaster equations fail the Painlevé test [11]. This suggests that the mixmaster may be chaotic, but the Painlevé test is also inconclusive.…”
mentioning
confidence: 99%
“…In short, Lyapunov exponents are not reliable indicators of chaos in general relativity. Using a different approach, it was shown that the mixmaster equations fail the Painlevé test [11]. This suggests that the mixmaster may be chaotic, but the Painlevé test is also inconclusive.…”
mentioning
confidence: 99%
“…By a proper canonical reescaling of the variables in (11) and (19) it is easy to see that these constant energy surfaces are hyperspheres and that the constants of motion Q 1 , Q 2 and Q 3 = (E rot1 − E rot2 ) satisfy the algebra of the three dimensional rotation group under the Poisson bracket operation, namely,…”
mentioning
confidence: 99%
“…It is worth remarking that the linearization of this canonical transformation about the critical point E yields exactly the linear transformation (11), and that the variables (y, p y , z, p z ) correspond to the primed variables (K ′ , Y ′ , L ′ , Z ′ ) defined on the S 3 center-center manifold about a linear neighborhood of the critical point. The variable x is obviously the average scale factor of the model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analytic integrability of Class A has been studied in previous works by several authors. [5][6][7][8][9][10][12][13][14][15][16][17] Here, our aim is to study the analytic integrability of all Bianchi models of class B in the variables ðx 1 ; x 2 ; x 3 ; x 4 ; x 5 ; x 6 Þ. In our study, we will use the following result, see Ref.…”
mentioning
confidence: 99%